Complex Formation between Aluminum(III) and Hydroxysalicyclic Acid Derivatives in Aqueous Solution - Turkel, Naciye; Ozer, Ulviye (Asian Journal of Chemistry, 2010)
Equilibria between aluminum(III) and hydroxysalicylic acids, (H3L), (2,X-DHBA, X = 4-6) were investigated in 0.1 M (NaCl) medium at 25.0 ± 0.1ºC. pH-Potentiometric solution speciation measurements were performed within the limits 2 ≤ pH ≤ 10 and Al(III) to ligand ratios were within the ranges 1 : 1 to 1 : 10. The stoichiometries of the formed complexes between Al(III) and these hydroxysalicylic acids were defined by means of spectroscopy. The results of potentiometric titrations were analyzed with two different computer programmes: BEST and RANA. All data can be explained with the occurrences of binary Al(HL)+ and Al(HL)(OH) mixed hydroxo complexes and their formation constants were found as: log β = 8.67 ± 0.02, 9.24 ± 0.02, 10.87 ± 0.01 and log b = 5.16 ± 0.04, 4.69 ± 0.04, 4.73 ± 0.04, respectively. The formation constants and the stoichiometries of Al(III)-2,X-DHBA complexes were compared to the values resulted in earlier studies of aluminium(lll)-2,XDHBA systems.